Biomechanical analysis for five fixation techniques of Pauwels-III fracture by finite element modeling. (September 2020) - Peng, Matthew Jian-Qiao; Xu, HongWen; Chen, Hai-Yan; Lin, Ze; Li, XinXu; Shen, ChuLong; Lau, YongQiang; He, ErXing; Guo, YueMing
Highlights: Femoral neck fracture problematic. Choose best Pauwels-III implant by comparison. Stress & displacement of 5 implants analyzed. Locking Plate/HemiArthroplasty is recommended as optimization. Preoperative strategy by simulation provides acute correction. Abstract: Background and objectives: There are many fixation methods for Pauwels- III fracture, the most common implants are Locking Plate (LP), Dynamic Hip Screw (DHS), Multiple Lag Screw (MLS), and mixed fixture (DHS+MLS) implants, the common procedure is HemiArthroplasty (HA). However, how these fixtures biomechanically function is not clear. The aims of this study are to compare the mechanical behaviors of these five implants by finite element modeling and determinate the most suitable procedure for individuals with Pauwels- III fractures. Methods: We gathered 20 sets of femur images from CT scans in the *.dicom format first, and then processed them by using reverse engineering software programs, such as Mimics, Geomagic Studio, UG-8, Pro-Engineer and HyperMesh. Finally, we assembled and analyzed the five types of fixture models, the LP, DHS, MLS, DHS+LS and HA models, by AnSys. Results: These numerical models of Pauwels III fractures, including fixators and a simulative HA, were validated by a previous study and a cadaver test. Our analytical findings include the following: the displacements of all fixtures were between 0.3801 and 1.0834 mm, and the differences were not statistically significantly different; the resulting average peaks in stress were e(Ha) = 43.859 ≤ d(LP) = 60.435 ≤ b(MLS) = 68.678 < c(LS+DHS) = 98.478 < a(DHS) = 248.595 in Mpa, indicating that the stress of DHS and DHS+LS are greater than those of LP, HA and MLS, while the last 3 models were not significantly different. Conclusions: To optimize the treatment for Pauwels III factures clinically, HA and LP should be proposed. Graphical abstract: Image, graphical abstract